SAXS Studies of the Endoglucanase Cel12A from Gloeophyllum trabeum Show Its Monomeric Structure and Reveal the Influence of Temperature on the Structural Stability of the Enzyme - Miotto, Lis S.; Reis, Caio V. dos; Neto, Mario de Oliveira [UNESP]; Polikarpov, Igor (Mdpi Ag, 2014)
Endoglucanases are key enzymes applied to the conversion of biomass aiming for second generation biofuel production. In the present study we obtained the small angle X-ray scattering (SAXS) structure of the G. trabeum endo-1,4-beta-glucanase Cel12A and investigated the influence of an important parameter, temperature, on both secondary and tertiary structure of the enzyme and its activity. The CD analysis for GtCel12A revealed that changes in the CD spectra starts at 55 degrees C and the T-m calculated from the experimental CD sigmoid curve using the Boltzmann function was 60.2 +/- 0.6 degrees C. SAXS data showed that GtCel12A forms monomers in solution and has an elongated form with a maximum diameter of 60 +/- 5 angstrom and a gyration radius of 19.4 +/- 0.1 angstrom as calculated from the distance distribution function. Kratky analysis revealed that 60 degrees C is the critical temperature above which we observed clear indications of denaturation. Our results showed the influence of temperature on the stability and activity of enzymes and revealed novel structural features of GtCel12A.
Keywords: endoglucanase; Gloeophyllum trabeum; biophysics; circular dichroism; small angle X-ray scattering (SAXS); Kratky analysis